LITERATURE REVIEW : TARGET TEKANAN DARAH PADA PASIEN STROKE ISKEMIK DAN HEMORAGIK - Roswita Sisilia Tosi; Suparto Suparto; Reni Angeline (Jurnal MedScientiae, 2023)
Stroke is a disease that can cause disability and even death. The highest incidence of stroke occurs in China. There is impaired cerebral function in stroke. Stroke is divided into 2 types, namely ischemic stroke and hemorrhagic stroke. Hypertension is a risk factor that is often found. Target blood pressure in stroke patients is part of stroke management. This study method is a literature review that uses the method of searching articles in databases such as Google Scholar Engine, Pubmed, and ProQuest which are then analyzed as many as 13 of the 1,455 journals obtained. The results showed that hemorrhagic stroke patients with systolic blood pressure ≥160 mmHg had a higher mortality rate within 90 days. Patients with a target systolic blood pressure of <140 mmHg can reduce the risk of progressive intracerebral hemorrhage and improve patient functional outcomes. An intensive fall in systolic blood pressure <120 mm Hg is associated with an increase in ischemic lesions and acute neurologic damage. Systolic blood pressure ≥ 160 mmHg can worsen the patient's condition symptomatically within 2 hours after thrombolysis compared to systolic blood pressure <140 mmHg which gives better functional results and reduced mortality in ischemic stroke patients.